The Existence of CEFR Reception Competence of Communicative Language Activities in TikTok - Handayani, Armitha; Santosa, Imam (STAIRS: English Language Education Journal, 2024)
The Common European Framework of Reference for Languages (CEFR) provides a standardized measure of language proficiency, guiding language learning and assessment globally. With the increasing use of digital media, videos have become an influential tool in language acquisition. TikTok, as a popular social media platform, offers engaging content that may support language learning. However, limited research has explored how TikTok videos align with CEFR communicative competence descriptors. This study aims to analyze the CEFR competence level of reception communicative activities in TikTok videos using the illustrative descriptor scale. Employing a qualitative approach, the research utilizes ATLAS.ti software to analyze 200 TikTok videos collected through the hashtag #learnenglish. The findings reveal that the most frequently occurring descriptor is overall oral comprehension, appearing in 62 videos, while the A1 level is the most represented, accounting for 25% (50 videos). These results suggest that TikTok videos predominantly cater to beginner-level learners. The study highlights the potential of TikTok as a supplementary language learning tool and provides insights for future research on optimizing digital platforms for CEFR-aligned language education.